Psychiatric Co‐Morbidities Among Children and Adolescents With Headache: Findings From a Cross‐Sectional Study in Bangladesh - Sifat E. Syed; Mohammad S. I. Mullick (Brain and Behavior, 2025)
ABSTRACT Introduction Headaches in pediatric populations are increasingly recognized as being associated with psychiatric disorders, predicting poor clinical outcomes. Despite global evidence, data from South Asia, particularly Bangladesh, remain sparse, limiting region‐specific insights into this comorbidity. Methods This descriptive, cross‐sectional study was conducted in the Pediatric Neurology Departments of two tertiary care hospitals in Dhaka, Bangladesh, between July 2019 and March 2020. A total of 151 children and adolescents were assessed using the International Classification of Headache Disorders (ICHD‐III beta version) for headache classification and the validated Bangla version of the Development and Well‐Being Assessment (DAWBA) for psychiatric diagnoses. Results Tension‐type headache was the most common type of headache (62.9%), followed by migraines (16.6%). Psychiatric co‐morbidities were identified in 39.7% of participants, with 13.2% presenting with multiple psychiatric disorders. Anxiety disorders (19.9%) and depressive disorders (12.6%) were the most prevalent. Children experiencing frequent headaches had significantly higher rates of psychiatric co‐morbidities (p = 0.020, 95% CI: 0.000–0.042). Logistic regression analysis revealed headache frequency as a minor but noteworthy predictor of psychiatric co‐morbidity (OR = 1.06, 95% CI: 1.016–1.093). Conclusion This study highlights a high burden of psychiatric disorders among children and adolescents with headaches in Bangladesh, emphasizing the importance of psychiatric screening and multidisciplinary management approaches for pediatric headache. The findings provide valuable regional data and reinforce the need for pediatrician‐psychiatrist collaboration to improve outcomes.